(untitled) (Research, Society and Development, 2021)
Occupational risks are all actions that may cause a short or long-term problem or discomfort suffered by service providers in a workplace. Occupational exposure to residues of anesthetic gases can lead health professionals to contract serious adverse health problems. However low the dosage, these professionals are exposed, this exposure becomes chronic and causes irreversible damage to the genetic material. This study sought to analyze the scientific production about occupational risks, damage to genetic material and oxidative stress in view of the exposure to residues of anesthetic gases. It is an integrative literature review, with a qualitative approach, carried out from January to April 2021, in the databases: MEDLINE, LILACS and PUBMED. Articles available in full in Portuguese and English, related to the topic, published in the last 10 years and following the descriptors selected in the study were included. The analysis of the selected publications allowed us to apprehend that it is extremely important for Nursing to obtain practical and theoretical knowledge about this problem, based on what has already been published, so as to have security and knowledge, in order to detect early changes, facilitating interventions that reverse the damage caused to genetic material.